2002
DOI: 10.1002/jcb.10274
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes induced by extracellular matrix are correlated with maturation of rat small hepatocytes

Abstract: Small hepatocytes (SHs), which are known to be hepatic progenitor cells, were isolated from an adult rat liver. SHs in a colony sometimes change their shape from small to large and from flat to rising/piled-up. The aim of the present study is to clarify whether the alteration of cell shape is correlated with the maturation of SHs and whether extracellular matrix (ECM) can induce the morphological changes of SHs. We used liver-enriched transcription factors (LETFs) such as hepatocyte nuclear factor (HNF) 4 alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 32 publications
(43 reference statements)
2
45
0
Order By: Relevance
“…Next, we examined whether SHs could proliferate in serum-free medium. Although we reported that SH colonies could expand in serumfree medium after re-plating SH colonies 4,16 , it was very difficult for SHs in serum-free medium to grow to form colonies on conventional dishes. When we used serum-free DMEM/F12 and HA-coated dishes, many colonies developed (Fig.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we examined whether SHs could proliferate in serum-free medium. Although we reported that SH colonies could expand in serumfree medium after re-plating SH colonies 4,16 , it was very difficult for SHs in serum-free medium to grow to form colonies on conventional dishes. When we used serum-free DMEM/F12 and HA-coated dishes, many colonies developed (Fig.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…Although the cells are less than half the size of mature hepatocytes (MHs), they possess hepatic characteristics 1 . SHs can clonally proliferate to form a colony and can differentiate into MHs by interacting with hepatic non-parenchymal cells (NPCs) 2,3 or as a result of treatment with gel derived from Engelbreth-Holm-Swarm sarcoma 4 . Thus, we consider that SHs may be 'committed progenitor cells' that can further differentiate into MHs.…”
Section: Introductionmentioning
confidence: 99%
“…The following Lightcycler PCR amplification protocol was used: 95°C for 10 minutes, and 45 amplification cycles (95°C for 5 seconds, 60°C for 10 seconds, 72°C for 5 seconds). Amplification was followed by melting curve analysis to verify the presence of a single PCR product [34]; 18S was amplified as a reference gene using the same protocol.…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%
“…This stimulation is maximal in the presence of glucocorticoids (19). Also, SerDH is considered a marker of liver maturation and is involved in regulating the development of different tissues (48). Previously (30), we have demonstrated that SerDH activity, as well as the protein and mRNA levels, fell in rat liver during chronic liver injury induced by thioacetamide.…”
mentioning
confidence: 73%